1997
DOI: 10.1016/s0886-3350(97)80155-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of against-the-rule astigmatism to uncorrected near acuity

Abstract: In pseudophakia, low, simple, ATR myopic astigmatism is better than WTR astigmatism because it provides superior uncorrected near visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 3 publications
4
64
6
Order By: Relevance
“…We also confirmed the intensified presence of corneal aberrations at an elderly age. It is well known that mild ATR myopic astigmatism can be beneficial to uncorrected near acuity in pseudophakic eyes, 34 although in our smaller cohort of patients, no correlation was found between the subjective accommodation amplitude and the direction of astigmatism.…”
Section: Discussioncontrasting
confidence: 73%
“…We also confirmed the intensified presence of corneal aberrations at an elderly age. It is well known that mild ATR myopic astigmatism can be beneficial to uncorrected near acuity in pseudophakic eyes, 34 although in our smaller cohort of patients, no correlation was found between the subjective accommodation amplitude and the direction of astigmatism.…”
Section: Discussioncontrasting
confidence: 73%
“…Traditionally it has been perceived that residual myopic against the rule cylinder may improve uncorrected near vision. 5 In a study conducted recently at our centre, it was seen that myopic astigmatism, up to 1D, in any axis, helps to partially restore uncorrected near visual acuity to some extent but with a proportional loss of distance acuity in pseudophakic eyes with monofocal IOL implant. However, uncorrected myopic astigmatism more than 1 D results in a large loss of distance acuity at no additional benefi t to near acuity.…”
mentioning
confidence: 97%
“…So it depends on patient cooperation and understanding. Subjective methods were found to be more reliable for measuring apparent accommodation according to Langenbucher et al 16 Many previous researches confirmed that the amplitude of apparent accommodation is correlated with different factors including; depth of focus 17,18 , pupil diameter 4,19 , degree of corneal astigmatism 20 , corneal multifocality and aberrations 21,22 , and IOL axial forward movement. 23,24 Depth of focus is an intrinsic characteristic of all optical systems that was considered to be one of the most significant factors of apparent accommodation.…”
Section: Discussionmentioning
confidence: 99%